Reviewing Victimology in the Doxing Case of an Indonesian Virtual Youtuber - Alvan Rahfiansyah Lubis; Ine Fauzia; Tajul Arifin (Indonesian Journal of Multidisciplinary Science, 2023)
The rapid development in technology has caused a revolution in the entertainment world in Indonesia. This development created a new profession called virtual Youtuber. A virtual Youtuber is someone who has another identity and hides behind an animation which is often called an avatar, therefore a phenomenon arises where virtual Youtubers are spread their personal data which is commonly called doxing. Therefore, this paper wants to analyze how the review of victimology in Indonesia and how the review of victimology on doxing cases against virtual Youtubers (Chloe Papua, Naminae Sae, and also Fay Kuroda) in Indonesia. By using the juridical-empirical research method where legal research through the formulation or application of normative law in a group of people who are in and involved with virtual Youtubers. The most important finding in this study is how the justice system in Indonesia which uses an offender oriented system where the criminal process is more likely to focus on the perpetrator does not provide a restorative justice effect, therefore it is often encountered that victims do not know the full extent of the rights they should have obtained,  this condition makes it limited to law enforcement that is applied but far from being fair to victims.